Bridging Tradition and Modern Learning: The Effectiveness of the al-Miftah li al-Ulum Method in Kitab Kuning Instruction - Achmad Lubabul Chadziq; Zayad Abd. Rahman (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
Abstract: One of the main keys to understanding kitab kuning (classical Islamic texts) is mastery of Arabic grammar, namely nahwu and sharaf. However, field observations show that many beginner students (santri) face difficulties in learning these two branches of knowledge. Conventional, text-oriented learning processes with minimal practical approaches often make most students feel burdened and lose motivation. As a result, the ability to read and comprehend kitab kuning, which is in fact the main goal, has declined significantly. This situation has become a particular concern among pesantren caretakers and teachers. They face major challenges in maintaining the quality of students’ scholarly competence amid an era demanding efficiency and practicality in teaching and learning. Therefore, innovation in nahwu and sharaf learning methods that are fast, practical, and applicable is needed so that students can more easily understand Arabic structures and read kitab kuning effectively. Using a descriptive-analytic method, this paper seeks to portray the implementation of the al-Miftah li al-Ulum method at Madrasah Diniyah of the Tarbiyatut Tholabah Islamic boarding school as an effort to improve the ability to read kitab kuning. The results of this study indicate that the use of this method is highly effective in increasing students’ learning interest and competence in reading classical texts, especially Fath al-Qarib.